PHYSICAL ACTIVITIES PERFORMED BY CHILDREN OF THE KAINGANG TRIBE OF THE INDIGENOUS LAND RIVER OF THE SNAKES (Fiep Bulletin - online, 2014)
The objective was to identify the physical activities performed by children, between 8 and 9 years old, of the Kaingang tribe of the Indigenous Land River of the Snakes, located in the municipality of Nova Laranjeiras, Parana, Brazil. The study was characterized as being descriptive and cross-sectional. The instrument of measure used, was the interview, applied to 63 children, accompanied by their guardians. The results indicate that among the boys the following games stand out:  playing with toy cars, run and catch, swimming, playing with marbles and playing soccer .For the girls: playing with dolls, role games (little house, school), run and catch, swimming and playing soccer and volleyball. The following labor activities stand out among the boys: collecting firewood, harvesting corn and hoeing. For the girls: washing the dishes, cleaning the house and doing the laundry. Activities relating to games and plays are learned informally, however they could be enriched through formal activities learned during Physical Education classes or in programmed after school activities, including games and plays of their own ethnic group and other indigenous ethnic groups. After school physical activities are very important, but, as they are indigenous groups, these activities should be proposed with caution, in order to avoid interferences in the daily routine of the village and letting the children fulfill the daily functions of their culture, such as the labor activities that serve as learning for their future adult activities.
Keywords: labor activities; games; indigenous